Pengaruh Corporate Governance, Profitabilitas, Leverage, dan Kualitas Audit Terhadap Real Earnings Management - Devi, Clarissa Maya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Tarumanagara, 2018)
Abstract :The purpose of this study is to examine the affects of corporate governace, profitability, leverage and audit quality on real earnings management in manufacturing company listed in Indonesia Stock Exchange during period 2014 until 2016. The total sample of this research was 63 manufacture companies. The result of this research shows that profitability and audit quality has positive and significant affects on real earnings management, but corporate governance and leverage has no effect on real earnings management. Keywords :Real Earnings Management, Corporate Governance, Audit Committee Meetings, Audit Committee of Accounting Experts, Profitability, Leverage, Audit Quality.